An In-Depth Study on Load Distribution Characteristics of the Planetary Threaded Roller Bearing. (10th November 2020) - Zheng, Shicheng; Fu, Yongling; Pan, Junlin; Li, Linjie; Wang, Deyi
Abstract : To lay a solid base for the property analysis and structural optimization on the high-strength planetary threaded roller bearing (PTRB) which is commonly used in mountain-walking robotic platforms, this research mainly focuses on characterizing the load distribution on the bearing under different loading conditions. An in-depth analysis was performed on the structural components and the contact characteristics of the PTRB. Based on the space meshing and Hertz contact theories, the elastic deformation of both inner and outer rings and the threaded roller was evaluated when the bearing was subjected to an axial or radial load. Meanwhile, a calculation method was proposed to obtain the load distribution coefficients of the PTRB according to the compatibility equations. In this way, an analysis on the load distribution of the PTRB was provided on the basis of the theoretical models. The results indicated that the effect of the applied load was very limited on the load distribution coefficients under an axial loading condition. The maximum value was found at the first thread of the inner ring-threaded roller contact pair, while no obvious effect was found when the bearing was carrying a radial load. It was indicated that the uniformity of the load distribution was effectively improved for axial and radial loading conditions through adjusting the distance between threads and increasing the threaded roller numbers, respectively. Therefore, both the rated load and the life cycle of the bearing can be further improved, while the friction torque can be minimized within a limited space. The research provides an important guidance for the property analysis, design, and optimization of the PTRB.